Management Interventions for improving economic efficiency of irrigation water resource in Andhra Pradesh, - K.N. Ravi Kumar,; D. Srinivas, (Journal of Agricultural Extension Management, 2025)
The story of food security in the 21'1 century in India is likely to be closely linked to the story of water security. In the coming decades, the farmers will need to produce enough food to feed more people in the country, yet there are virtually no untapped and cost-effective sources of water for them to draw on as they face this challenge. Moreover, the farmers will have to face heavy competition for this water from non-agricultural sector usage. Irrigation played a vital role to achieve food security and sustainable livelihoods especially in developing countries like Indi a during the Green Revolution period through increased income, improved health and nutrition locally and by bridging the gap between production and demand nationally. But today, this essential resource is under severe threat